Chemical composition and acaricidal activity of essential oils from two species of the genus Bauhinia that occur in the Cerrado biome in Brazil. Issue 1 (2nd January 2020) - da Silva, Karla L. C; da Silva, Milena M. C; de Moraes, Marcilio M.; da Camara, Claudio A. G.; dos Santos, Maria L.; Fagg, Christopher W.
ABSTRACT: Essential oils from the leaves of Bauhinia rufa and B. dumosa collected from the Cerrado biome in central Brazil were obtained by hydrodistillation and analyzed using GC and GC/MS. Both oils had a predominance of sesquiterpenes ( B. rufa : 95.3 ± 0.5%; B. dumosa : 97.2 ± 1.1%). β -Caryophyllene (15.8 ± 0.5%), epi-α -cadinol (12.8 ± 0.4%), γ -muurolene (12.2 ± 0.4%) and α -cadinol (10.0 ± 0.5%) were identified as the major constituents of the B. rufa oil, whereas germacrene B (37.6 ± 1.2%) and ( E )-nerolidol (29.1 ± 0.6%) were the major constituents of the B. dumosa oil. Both oils were toxic to Tetranychus urticae by fumigation ( B. rufa : LC50  = 2.76 µL/L of air; B. dumosa : LC50  = 0.97 µL/L of air) and residual contact ( B. rufa : LC50  = 30.46 µL/mL; B. dumosa : LC50  = 16.44 µL/mL). The results of the two-choice method revealed that the oils affect the behavior of the mite, interfering in its feeding and egg-laying preferences.